2019
DOI: 10.1177/0734242x19860895
|View full text |Cite
|
Sign up to set email alerts
|

Biomass co-pyrolysis: Effects of blending three different biomasses on oil yield and quality

Abstract: In the present study, pyrolysis and co-pyrolysis of sugarcane bagasse, poppy capsule pulp, and rice husk were conducted in a fixed bed reactor at 550⁰C in nitrogen atmosphere. The moisture (5%–8%), ash (4%–17%), volatile matter (60%–76%), and fixed carbon analyses (11%–24%) of the utilized biomass were conducted. The decomposition behavior of biomasses due to the heat effect was investigated by thermogravimetric analysis/differential thermal analysis . In the pyrolysis of biomasses separately, the highest bio-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 29 publications
1
9
0
1
Order By: Relevance
“…The highest bio-oil content was found with the highest final process temperature of 500 °C, using pure beet pulp pellets as the feedstock material. Synergy as a result of co-pyrolysis was not only related to the amount of gas but it could also, with 50% beet pulp content and 400 °C temperature, have effected lowering the bio-oil content, similar to another study [ 35 ]. No clear symptom of synergy was observed concerning the ash content of the products as described by the authors of the paper [ 32 ].…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The highest bio-oil content was found with the highest final process temperature of 500 °C, using pure beet pulp pellets as the feedstock material. Synergy as a result of co-pyrolysis was not only related to the amount of gas but it could also, with 50% beet pulp content and 400 °C temperature, have effected lowering the bio-oil content, similar to another study [ 35 ]. No clear symptom of synergy was observed concerning the ash content of the products as described by the authors of the paper [ 32 ].…”
Section: Resultssupporting
confidence: 79%
“…FTIR spectra (Fourier transform infrared spectroscopy) showed that the process of beet pulp pyrolysis produces not only large amounts of gases, such as CO 2 , CO, H 2 O and CH 4 , and H 2 , but also many volatile aldehydes, ketones, organic acids, and alkanes, and co-pyrolysis involving the pyrolysis of several feedstock materials mixed compared to the pyrolysis of individual feedstock may also produce a synergistic effect concerning some products resulting from the process. This could be an increased yield of bio-oil [ 35 ] or an increased proportion of the ash that occurred during the co-pyrolysis of beet pulp with lignite [ 32 ]. An increase in the mass proportion of defecation lime in samples with beet pulp resulted in an increase in the mass of biochar from 29.4 to 51.6%.…”
Section: Introductionmentioning
confidence: 99%
“…Hopa et al studied the effects of temperature on bio-oil yield and its calorific value obtained from the pyrolysis of PCP in a fixed-bed reactor [6]. In another study, they investigated the pyrolysis and co-pyrolysis behavior and bio-oil yields of sugarcane bagasse, PCP, and rice husk mixtures in a fixed bed reactor [7]. Thermochemical conversion processes developed for coal and biomass mixtures can reduce fossil fuel consumption and contribute to the spread of commercial-scale applications of biomass.…”
Section: Introductionmentioning
confidence: 99%
“…In the present context, fossil fuels are the major source of energy, but are being depleted at an ever-increasing rate and are expected to be exhausted shortly. Furthermore, utilization of fossil fuels, which emit noxious gases that pollute the environment and result in the accumulation of carbon dioxide gas in the atmosphere, is the major cause of the greenhouse gas effect (Hopa et al, 2019). In contrast, biomass is an important resource for renewable energy, and its use is becoming increasingly significant for climate protection when compared with other renewable energy sources.…”
Section: Introductionmentioning
confidence: 99%